ENAMEL HYPOPLASIA AS A STRESS SIGNAL: UNVEILING PALEOENVIRONMENTAL STRESS EPISODES IN THE SIWALIK’S SUIDS OF PAKISTAN FROM THE MIDDLE MIOCENE TO EARLY PLEISTOCENE - Iqra Manzoor; Sadaf Aslam; Abdul Majid Khan; Muhammad Irfan; Muhammad Nouman; Naveed Ahmed (Journal of Animal and Plant Sciences, 2024)
Numerous paleontologists have used research on tooth enamel hypoplasia as a stress signal when assessing paleoenvironments. The goal of the current study was to identify and evaluate stress periods that occurred in the middle Miocene to early Pleistocene eras of the Siwaliks of Pakistan by analyzing enamel hypoplasia in eight extinct suids species: Listriodon pentapotamiae, Tetraconodon minor, Sivachoerus prior, Hippohyus lydekkeri, Hippohyus sivalensis, Hippopotamodon sivalense, Tetraconodon magnus, Propotamochoerus hysudricus. All suid species from all time intervals between 14.2 and 0.6 million years old (Myo) were analyzed, with the exception of those from the 11.2-9.0 Myo time frame (late Miocene), when no suids were found to show enamel hypoplasia. Enamel hypoplasia was the most common in suids from the middle Miocene Siwalik (63%), followed by those from the early Pliocene to the Pleistocene (43%), the late Miocene to the Pliocene (25%), and the late Miocene to the early Pleistocene (33%). The percentage of incidence of E.H with respect to each species was 62.50% in Listriodon pentapotamiae, 50% in Sivachoerus prior and Hippohyus sivalensis, 33.33% in Hippohyus lydekkeri and Propotamochoerus hysudricus and 0% in Tetraconodon minor and Tetraconodon magnus. The prevalence of enamel hypoplasia during the Neogene and Quaternary in the Siwalik region provides evidence for the occurrence of stress episodes, while the proportion of hypoplastic enamel illustrates the relative intensity of these stresses. These stressful events brought on by a lack of food or nutrition happened because of the historical periods' drastic shifts in weather, vegetation, ecology, and wildlife. These stress periods, which occurred from the early Miocene to the Pleistocene, may have spurred the evolution and speciation of the Siwalik fauna, notably the mammals.
Keywords: Enamel hypoplasia; Stress signals; Paleoenvironment; Siwaliks; Suids